INFLUENCE OF Miscanthus × giganteus RHIZOME MASS ON THE CROP ESTABLISHMENT - Simić, Aleksandar S; Dželetović, Željko S; Andrejić, Gordana Z; Geren, Hakan F (Journal of Agricultural Sciences (Belgrade), 2019)
The aim of the present investigation was to assess the influence of rhizome mass of the bioenergy crop M. × giganteus on the success of plantation establishment and biomass yield in the first 10 years of cultivation. The experiment included three treatments with different rhizome masses: 10-20 g; 25-35 g, and 40-60 g. Planting density was 2 rhizomes m-2. The plants were harvested by mowing of the whole above-ground biomass each year in February. Of the total number of planted rhizomes, the least successful plantlet emergence was noticed with very low mass rhizomes. In the first season of cultivation, the greatest number of stems and crop height were encountered under the treatment with the highest rhizome mass. In the second season, crop heights were already almost equal. During the first two seasons, the highest biomass yields were recorded under the treatments with the highest rhizome masses. Although the analyzed parameters were highest with the rhizomes of 40-60g during the crop establishing stage, starting from the third season of cultivation, high yields of above-ground biomass may be obtained also with lower mass rhizomes. With the highest biomass yield (25.85±7.36 Mg DM ha-1), the crop established with rhizomes of 25-35 g is clearly standing out.